Mobilization and Leaching of Trace Elements (Fe, Al and Mn) in Agricultural Soils as Affected by Simulated Acid Rain - Nawaz, Rab; Parkpian, Preeda; Arshad, Muhammad; Ahmad, Farooq; Garivait, Hathairatana; Skhawat Ali, Adnan (Asian Journal of Chemistry, 2013)
In this study, the mobilization and leaching of iron, aluminum and manganese were evaluated as influenced by different rates of acid deposition on three agricultural soils (Korat, Pak Chong and Phon Pisai) of Thailand. In laboratory experiments, acidic solutions (pH 3.5, 3.0, 2.5 and 2.0) and unpolluted water (pH 7.0) were applied to soil columns over a period of 45 days. Basic properties of the investigated soil were determined before the experiment, while levels of target metals (Fe, Al and Mn) were determined before and after the experiment. The effluent was collected after every 5 days and analyzed for the target elements. Acid rain caused highly significant (p value < 0.001) leaching of all the investigated metals. Mobilization and leaching of Fe, Al and Mn increased with an increase in the acidity of applied solutions. Highest leaching of Fe occurred in Korat soil under all the applied acidic solutions. Leaching of Al was very high in Pak Chong and Phon Pisai soils. Quite high leaching of Mn was found in all the soils under treatment with a highly acidic solution (pH 2.00). Extractable contents of all the investigated elements changed considerably in all the soils. Behaviour of the target elements depended on soil texture, cation exchange capacity, soil reaction (acidity), sesquioxides, organic matter content, and the sulfate and nitrate adsorption capacity of the soil. Mobility of these elements can cause rhizotoxicity and their leaching by acid rain poses a threat to groundwater quality and environmental contamination.